The Power of Personality Traits in Allocation Decision-Making: A Secondary Analysis of a Laboratory Experiment - Lilla Tolnai (Junior Management Science (JUMS), 2021)
Individual differences have been addressed by many authors in social sciences, however personality has been neglected. The purpose of this thesis is to investigate the role of personality in social decision-making situations. Prior researches on the role of personality either focused on how personality influences social and economic preferences or on the link between personality and influence in social decision-making. The present thesis intends to combine these two aspects with the help of a secondary analysis of a bargaining experiment. To test personality, the Five Factor Model was included and social preferences were measured with the help of social value orientation. The findings show that two personality dimensions (Agreeableness and Conscientiousness) indicate social preferences and four personality dimensions (Agreeableness, Extraversion, Neuroticism, and Conscientiousness) influence the ability to use structural power. Furthermore, it has been found that the link of personality and bargaining behavior is moderated by social preferences. The findings of the present thesis provide various theoretical and empirical implications for personality psychology, human resource management, and organizational behavior.
Keywords: 650; Social decision-making; fairness; personality; Five Factor Model; social value orientation